Designing programmes of physical activity through sport: learning from a widening participation intervention, 'City of Football' - Stephen Zwolinsky; Nicola Kime; Andy Pringle; Paul Widdop; Jim McKenna (BMC, 2018)
Abstract Background Implementation profoundly influences how well new audiences engage with sport-based physical activity programmes. Recognising that effective implementation relies on concurrently generating supportive contexts, systems and networks for the least engaged 'target' groups; this paper aims to address what underpins children's (non) engagement with football-based physical activity. Methods An observational research design, using a non-probability sample of N = 594 primary and secondary schoolchildren assessed outcomes of a three-year 'City of Football' (CoF) programme. Pupils self-reported football participation, personal friendship networks and exposure to six concurrent sources of influence (SoI). A 2-step hierarchical cluster analysis and univariate analyses assessed between-cluster differences. Results Girls played football least regularly (χ2 [4] = 86.722, p = 0.000). Overall, participation was significantly associated with personal networks engaged in football. Boys' personal networks were more stable and structurally effective. Football participation was also positively and linearly association with SoI scores. Girls and pupils with no personal networks around football reported the lowest SoI scores. Three clusters emerged, dominated by social network influences. The Traditional Market (n = 157, 27.7%) comprised 81.7% boys; they regularly played football, had the most effective network structure and scored highly across all six domains of SoI. The Sporadically Engaging Socialisers (n = 190, 33.5%) comprised 52.9% girls who rarely played football, reported low SoI scores and an inferior network structure. In the Disconnected cluster (n = 220, 38.8%), 59.3% were non-footballing girls who reported the lowest motivation and ability SoI scores; and no personal networks engaged in football. Conclusions This study reveals new insights about the primacy of social network effects for engaging children in football-based physical activity programmes. With little or no attention to these social-oriented issues, such interventions will struggle to attract 'target' children, but will readily engage already well-connected, experienced football-playing boys. The challenge for drawing non-footballing children into football-based interventions lies with engaging children - especially girls - whose social networks are not football-focused, while they also find football neither personally motivating nor easy to do.